A OneStep Solution to Fix and Stain Cells for Correlative Live and Fixed Microscopy. Issue 11 (26th November 2021) - Velle, Katrina B.; Fermino do Rosário, Carline; Wadsworth, Patricia; Fritz‐Laylin, Lillian K.
Abstract: Correlating the location of subcellular structures with dynamic cellular behaviors is difficult when working with organisms that lack the molecular genetic tools needed for expressing fluorescent protein fusions. Here, we describe a protocol for fixing, permeabilizing, and staining cells in a single step while imaging on a microscope. In contrast to traditional, multi‐step fixing and staining protocols that take hours, the protocol outlined here achieves satisfactory staining within minutes. This approach takes advantage of well‐characterized small molecules that stain specific subcellular structures, including nuclei, mitochondria, and actin networks. Direct visualization of the entire process allows for rapid optimization of cell fixation and staining, as well as straightforward identification of fixation artifacts. Moreover, live imaging prior to fixation reveals the dynamic history of cellular features, making it particularly useful for model systems without the capacity for expressing fluorescent protein fusions. © 2021 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol : Fixing, permeabilizing, and staining mammalian cells in one step on the microscope